Research on Education for Values in Schools: An Academic Review and Classification - Srivastava, Manish Kumar; Chaudhry, Harish; Sota, Shikha; Tanwar, Anshika Singh (INDIAN EDUCATIONAL REVIEW, 2021)
This article reviews the research papers published in the educational journals on values education in schools from 1995 to 2020. The report aims to present a categorisation of literature with a comprehensive bibliometric analysis. Five hundred eighty-one relevant research papers are selected from the SCOPUS database and analysed using VOS viewer software. This research investigates how values education research has developed over this period in critical areas, significant authors, research types, and tools and methodologies applied. There is a dearth of published literature in this field. The co-citation analysis of cited references has revealed six research clusters related to values education researches in the school context. This study identified the significant authors, journals and organisations in this area. This study dispenses the first such review and consequently presents the most recent taxonomy and literature study helpful to researchers, educationists and policymakers.